The Ã 1B2u-X̃1Ag electronic absorption spectrum of 1,2,4,5-tetrafluorobenzene: rotational band contour and vibrational analysis relating to non-planarity in the Ã state - Hollas, J. Michael; Hussein, Mohd Zobir (Elsevier, 1988)
The vapour phase electronic absorption spectrum of 1,2,4,5-tetrafluorobenzene, in the region of the S1-S0 band system, has been photographed under conditions of high resolution. Computer simulation of the observed rotational contours has shown that all the most intense bands are type A and, therefore, that the electronic assignment is A ‘B2uX1Ag. The rotational constants in the A state are consistent with an out-of-plane angle of the C-F bonds of 11+4”. This is consistent with the result obtained by Okuyama et al., from the supersonic jet spectrum, that the fluorine atoms are out-of-plane in a “butterfly” configuration. Obser- vation of hot bands of the butterfly vibration, which are frozen out in the jet spectrum, provides strong support for the W-shaped potential function proposed by Okuyama et al. for this vibration in the A state.